Climate change, forced migration, and international law - McAdam, Jane, 1974- (Oxford : Oxford University Press, 2012)
This is a key study into whether 'climate change refugees' are protected by international law. It examines the reasons why people do or do not move; how far climate change is a trigger for movement; and whether international responses, such as creating new treaties and new institutions, are appropriate solutions in this context.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Environmental refugees -- Legal status, laws, etc; Climatic changes -- Environmental aspects